Telemedicine and Digital Health in the Future of Midwifery Care - Astuti, Dhesi Ari; Langputeh, Prapaporn; Sulisworo, Dwi (The Indonesian Institute of Science and Technology Research, 2023)
Telemedicine and digital health have emerged as transformative midwifery and maternal healthcare technologies. This study employs a comprehensive bibliometric analysis to explore the current research landscape at the intersection of telemedicine, digital health, and midwifery. The methodology involves an initial search in the Dimensions database using the keywords